Rates of new-onset psoriasis in patients with rheumatoid arthritis receiving anti-tumour necrosis factor α therapy: results from the British Society for Rheumatology Biologics Register. Issue 2 (2nd April 2008) - Harrison, M J; Dixon, W G; Watson, K D; King, Y; Groves, R; Hyrich, K L; Symmons, D P M; ,
Abstract : Background: Anti-tumour necrosis factor (TNF)α treatments improve outcome in severe rheumatoid arthritis (RA) and are efficacious in psoriasis and psoriatic arthritis. However recent case reports describe psoriasis occurring as an adverse event in patients with RA receiving anti-TNFα therapy. Objectives: We aimed to determine whether the incidence rate of psoriasis was higher in patients with RA treated with anti-TNFα therapy compared to those treated with traditional disease-modifying antirheumatic drugs (DMARDs). We also compared the incidence rates of psoriasis between the three anti-TNFα drugs licensed for RA. Methods: We studied 9826 anti-TNF-treated and 2880 DMARD-treated patients with severe RA from The British Society for Rheumatology Biologics Register (BSRBR). All patients reported with new onset psoriasis as an adverse event were included in the analysis. Incidence rates of psoriasis were calculated as events/1000 person years and compared using incidence rate ratios (IRR). Results: In all, 25 incident cases of psoriasis in patients receiving anti-TNFα therapy and none in the comparison cohort were reported between January 2001 and July 2007. The absence of any cases in the comparison cohort precluded a direct comparison; however the crude incidence rate of psoriasis in those treated with anti-TNFα therapy was elevated at 1.04 (95% CI 0.67 to 1.54) per 1000 person years compared to the rate of 0 (upper 97.5% CI 0.71) per 1000 person years in the patients treated with DMARDs. Patients treated with adalimumab had a significantly higher rate of incident psoriasis compared to patients treated with etanercept (IRR 4.6, 95% CI 1.7 to 12.1) and infliximab (IRR 3.5, 95% CI 1.3 to 9.3). Conclusions: Results from this study suggest that the incidence of psoriasis is increased in patients treated with anti-TNFα therapy. Our findings also suggest that the incidence may be higher in patients treated with adalimumab.